Camcridge O level second language Urdu 3248 paper 1 : Kawish e Jadeed - Iqbal, Ghulam Waris (karachi : Danesh publications, 2024)
The Cambridge O Level Second Language Urdu 3248 - Kawish e Jadeed is a study guide designed for students preparing for the Cambridge O Level Urdu exam (subject code 3248). This book aims to help learners develop their proficiency in reading, writing, and comprehension skills in the Urdu language.
The main goal of Kawish e Jadeed is to provide students with a comprehensive resource for thorough exam preparation. It is designed to ensure that learners are well-versed in both the linguistic and cultural aspects of the Urdu language as required for the Cambridge O Level exam. This book is widely used by students, teachers, and tutors to enhance Urdu language skills in preparation for O Level exams.
Keywords: Urdu - past exam paper 1; Cambridge olevel - Urdu past exam paper 1